Evaluation The Antimicrobial Activity of Camels Urine Against some Pathogenic Bacteria and Yeasts - Rahem. E. AL-Zaiadi; Iman Thapti; jenan Rasaak (Kufa Journal for Veterinary Medical Sciences, 2016)
This study was carried out to examine the antimicrobial activity of  the unfiltered fresh urine and filtered using Millipore upon pathogenic bacteria and yeasts, The camel’s urine was collected from female camel Camelus dromedaries of age 5 years, at a barn in the Faculty of Agriculture - Almothana university and from the Western Desert of Samawah .The physical content of the samples was been studying, colures was yellow in the tow samples , and been dark with stored .  pH  6.11 for a barn in the Faculty of Agriculture and 6,67 for Western Desert of Samawah samples.